2020
DOI: 10.21273/horttech04454-19
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Home Lawn Fertilizer Choice in the United States

Abstract: Home lawn fertilizer use throughout the United States is coming under increased scrutiny due to potential negative environmental impacts. A better understanding of how consumer perceptions and socio-demographics impact their choices of types of lawn fertilizers can aid industry stakeholders when marketing products. This research uses a nationwide survey to evaluate factors that impact respondents’ choice of lawn fertilizer brands. Respondents with home lawns selected the lawn fertilizer brands they pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
1
8
1
Order By: Relevance
“…Several of the estimated coefficients on demographic and other causal variables (defined in Table 1) are significant in the structural equation for Ecopract (Table 2). Contrary to findings by Behe et al (2010) and Grebitus et al (2017), but similar to those by Campbell et al (2020), female gender has a negative influence on propensity to use ecofriendly gardening practices (Ecopract). As with several prior studies' findings (Behe et al, 2010;Yue et al, 2010Yue et al, , 2016, higher educational attainment (College) was found to have a positive influence on Ecopract.…”
Section: Respondent Summary Statisticscontrasting
confidence: 69%
See 3 more Smart Citations
“…Several of the estimated coefficients on demographic and other causal variables (defined in Table 1) are significant in the structural equation for Ecopract (Table 2). Contrary to findings by Behe et al (2010) and Grebitus et al (2017), but similar to those by Campbell et al (2020), female gender has a negative influence on propensity to use ecofriendly gardening practices (Ecopract). As with several prior studies' findings (Behe et al, 2010;Yue et al, 2010Yue et al, , 2016, higher educational attainment (College) was found to have a positive influence on Ecopract.…”
Section: Respondent Summary Statisticscontrasting
confidence: 69%
“…Khachatryan et al (2017) showed that households with relatively higher income were less likely to purchase conventionally grown florals when environmentally friendly alternatives were available. In addition, other studies found a positive correlation between income and preferences for sustainable plant options (Rihn et al, 2016) and packaging (Yue et al, 2010); however, Campbell et al (2020) found that income had a negative effect on probability that consumers would choose a sustainable/organic brand of fertilizer. Note, in this study we use gardening supplies expenditures as a proxy for income.…”
Section: Previous Researchmentioning
confidence: 92%
See 2 more Smart Citations
“…Also, the importance of digestate-specific proenvironmental levels of attributes [25] is mirrored in the WTP results. The importance of the attribute "organic" and differences between consumer segments has also been shown in a study on how U.S. consumers make their choices on home lawn fertilizers [82]. However, the mixed results for guano show that, for some attributes, it might be less than clear which level is best from an environmental point of view.…”
Section: Contextualization With Previous Studies and Avenues For Future Researchmentioning
confidence: 91%